THE ISSUE OF ATTITUDE TO NATURE AND ENVIRONMENT IN ISLAM (TAMADDUN NURI JURNALI, 2024)
In this article, within the framework of Islamic teachings, the issue of the relationship of people to nature and the environment, their sources (the Holy Qur’an, hadiths), as well as the information presented in the scientific literature of the later period and the analysis of Internet sources, is revealed. In the study, the mutual harmony between man, nature and society, as a whole system, was thoroughly analyzed.